Contribution of students’ self-leadership in online learning activity to academic achievement during covid-19 pandemic - Gendon Barus; Paulus Yanuar Kharismawan; Anastasia Setyandari (Jurnal Konseling dan Pendidikan, 2022)
Are the students able to well lead themselves in online learning activity during the Covid-19 pandemic? This study aims 1). measuring how well the students' self-leadership abilities in online academic activities during the pandemic, 2). identify the qualities of students' self-leadership abilities that are weak/not present in online academic activities, and 3). explore whether or not there is a correlation/contribution of students’ self-leadership ability in academic activities to GPA during the pandemic? The research subjects were 210 students of the Guidance and Counseling study program at Sanata Dharma University. The data employed the Student Self-leadership Scale in Online Learning with 6 grades differential semantic model with an alpha reliability index of 0.956. The data were analyzed using descriptive categories and rPM correlation techniques. The results showed that some students were able to lead themselves in carrying out academic activities during the pandemic; 9 items of students’ self-leadership measurement were identified that were not optimal in online academic activities during the pandemic; and there was no correlation/contribution between students’ self-leadership abilities in online academic activities and GPA during the pandemic